Anthrax Lethal Toxin Inhibits the Production of Proinflammatory Cytokines. (27th March 2013) - Wu, Aiguo; Shiloach, Joseph; Alibek, Darya; Li, Lydia Yue; Bradburne, Christopher; Alibek, Ken
Abstract : In previous studies, we have found that anthrax lethal toxin (LeTx) induces apoptosis in both murine macrophages and human peripheral blood mononuclear cells (PBMCs). In this study, we further report that bacterial cell wall (CW) components of Bacillus (B.) anthracis are powerful inducers of proinflammatory cytokines from the PBMCs. These effects are deprived when the LeTx is present. The major causative element for this suppression is lethal factor (LF) rather than protective antigen (PA). These results indicate that the roles of LeTx in anthrax pathogenesis, particularly its effects on cytokine production, should be reevaluated as our findings and other reports are controversial to the conventional concept.